Adobe Flash Professional CS5 digital classroom - Gerantabee, Fred; AGI Creative Team (Indianapolis, IN Wiley, 2010)
Enhanced by video tutorials and lesson files on a companion DVD-ROM, fifteen self-paced lessons explore the new features and capabilities of Adobe Flash Professional
Includes index
1
Keywords: Flash (Computer file); Flash (Computer software); Computer animation; Computer animation; Computer graphics; Web sites -- Design; Web sites -- Design